Strategi Humas dalam Mengelola Opini Publik terhadap Santri Generasi Z - Nur Azizah azizah; Mohammad Zammil Qodiri (LP3M KH Yazid Karimullah Institute, 2024)
This study aims to examine public relations strategies in managing public opinion on the attitudes and behavior of Generation Z students. The main focus of this research is how the strategy has an impact on the positive image of the school and becomes a supporting factor in the development of the school. This research uses a qualitative approach with a narrative description type. Data collection techniques were conducted through observation, interviews, and documentation, which were then validated using method triangulation. The data were analyzed using the interactive analysis model of Miles and Huberman. The results showed that the public relations strategy was carried out by collaborating with all elements of the school through various excellent programs for all students, both from the students of Pesantren Al-Kaustar and from outside. One of the excellent programs that is the main attraction is the tahfidz Al-Quran program, which is attended by all students and is a differentiator from other schools in the Kraksaan area, Probolinggo. The education offered combines the latest science with Islamic values, so as to produce a superior and moral generation.